Small Sided Games 3vs3 Goalkeeper-Encouragement: Improve the Physical and Technical Performance of Youth Soccer Players - Hasanuddin Jumareng; Edi Setiawan; Amayra Tannoubi; Rola Angga Lardika; Ahmad Adil; Novri Gazali; Ruslan Abdul Gani; Farruh Ahmedov; Ahmet Kurtoğlu; Dan Iulian Alexe (Asociación Española de Ciencias del Deporte, 2024)
This study aims to investigate the effect of small sided games (SSG) 3vs3 Goalkeeper (GK)-encouragement (E) on increasing the level of physical and technical performance of youth soccer players. A true experiment with a randomized control trial (RCT) for 8 weeks was adopted. 24 youth soccer players from the positions of striker, midfielder and defender participated in this study. They were divided in two groups, SSG (n = 12, 17.33 ± 1.07 years) and SSG 3vs3 GK-E (n = 12, 18.00 ± 1.04 years). Instruments to measure physical performance included 20m sprint test, Illinois agility test and Multistage 20m fitness test, while technical performance was assessed through dribbling, passing and shooting tests. The results of the student's paired t-test showed that there were changes in physical and technical performance in SSG and SSG 3vs3 GK-E (all, p < .001) from the pre-test to the post-test. The 2-Way ANOVA with 2 × 2 repeated measures results showed that physical and technical performance had a main effect of "time" (p < 0.05), effect "training session" (p < 0.05), and an effect "interaction" (p < 0.05). This study confirms that SSG 3vs3 GK-E can be an alternative training in the future to increase the level of physical and technical performance in of youth soccer players.